Assessment of the impact on human health of the contamination of muña’s dam (1999)
In the last 30 years the Muña's dam has increased the content of organic material in decomposition. The population of Sibaté has perceived an association between this contamination and the occurrence of respiratory and dermic diseases, and cancer. To explain this situation was realized a preliminary environmental assessment, an exploratory ecologic study of mortality, a prevalence survey of morbidity, a cross-sectional study of metal absorption, and the sociocultural characterization of the population. The findings doesn't shown an abnormal profile in the morbidity and the mortality of this population. It was explained these conclusions and we suggest new studies to improve the understanding of the possible association between the polluted dam and human health.